2007
DOI: 10.1002/ptr.2083
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone supplementation attenuates hypertension and renal damage in nitric oxide deficient hypertensive rats

Abstract: The present study was undertaken to evaluate the protective effect of thymoquinone (TQ), the main constituent of the volatile oil from Nigella sativa seeds, in rats after chronic inhibition of nitric oxide synthesis with N(omega)-nitro-l-arginine methyl esters (l-NAME). Rats were divided randomly into different treatment groups: control, l-NAME, TQ and l-NAME + TQ. Hypertension was induced by 4 weeks administration of l-NAME (50 mg/kg/day p.o.). TQ was administered alone or in combination with l-NAME and conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 38 publications
2
56
0
1
Order By: Relevance
“…Immunodulation is probably one of the ways by which the oil achieves the results (Salem, 2005). Thymoquinone, the recently implicated active component of black seed oil (Tekeoglu et al, 2006;Khattab and Nagi, 2007) might be the cytotoxic constituent conferring trypanocidal properties on the oil. We are currently exploring this possibility along with the possibility of inactivating possible toxins extracellularly released by trypanosomes.…”
Section: Haematological Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodulation is probably one of the ways by which the oil achieves the results (Salem, 2005). Thymoquinone, the recently implicated active component of black seed oil (Tekeoglu et al, 2006;Khattab and Nagi, 2007) might be the cytotoxic constituent conferring trypanocidal properties on the oil. We are currently exploring this possibility along with the possibility of inactivating possible toxins extracellularly released by trypanosomes.…”
Section: Haematological Indicesmentioning
confidence: 99%
“…It is a phytotherapeutic known to reduce the risk to illness and disease by strengthening immune system and protecting the body (Hajhashemi et al, 2004;Tekeoglu et al, 2006). Recent reports however suggest that thymoquinone present in the oil might be the active component (Tekeoglu et al, 2006;Khattab and Nagi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…NS was reported to have a preventive effect on oxidative stress by causing to rise of antioxidant enzymes (Khattab & Nagi 2007;Yaman & Balikci 2010). The antioxidant activity of NS seeds and oil was basically dependent on its active constituent thymoquinone and carvacrol (Thippeswamy & Naidu 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] It plays a significant mitigatory role against various heavy metal induced toxicities. 25 The protective effect of TQ is attributed to its free radical scavenging activity, 26,27 Hence, TQ stands as an important candidate for therapeutic approach against Asinduced neurotoxicity as it can cross blood brain barrier. Govil et al (2012) demonstrated the suitability of Post Nuclear Supernatant (PNS) as an alternate in-vitro model for assessing ROS mediated oxidative stress induced heavy metal toxicity.…”
Section: Introductionmentioning
confidence: 99%